Pengaruh Kompetensi Dan Profesionalisme Terhadap Kinerja Pegawai Dengan Budaya Kerja Sebagai Variabel Moderasi Pada Dinas Pariwisata Pemuda Dan Olahraga Kota Payakumbuh - Roza, Elvia; Putri, Anne (Jurnal Ekonomika Dan Bisnis (JEBS), 2024)
This research aims to analyze and test the influence of competence, professionalism on performance with work culture as a moderating variable at the Payakumbuh City Youth and Sports Tourism Office. This type of research is quantitative research. This sample is all employees of the Payakumbuh City Tourism, Youth and Sports Department. The sampling method uses the census method, where all members of the population are used as research samples. This research uses primary data obtained through questionnaires delivered directly to all employees of the Payakumbuh City Tourism, Youth and Sports Department totaling 62 questionnaires and all respondents returned the questionnaires. The data was processed using Structural Equation Modeling (SEM) analysis using the SmartPLS application. The research results show that competence has a significant positive effect on employee performance. Then other results show that professionalism has a positive and significant effect on employee performance. Competency which is moderated by work culture has a negative and insignificant effect on employee performance. Meanwhile, professionalism moderated by work culture has a positive and insignificant effect on the performance of employees of the Payakumbuh City Tourism, Youth and Sports Department.